Are central sensitization symptoms and psychosocial alterations interfering in the association between painful TMD, migraine, and headache attributed to TMD? - Vale Braido, Guilherme Vinícius do [UNESP] (2023)
Objective: To determine if somatosensory function and symptoms related to central sensitization (CS) differed in individuals with painful temporomandibular disorders (TMD) according to the presence of migraine (MIG) or MIG + headache attributed to TMD (HAT). Materials and methods: This study evaluated 92 adults (20–65 years), presenting painful TMD. Standard diagnostic criteria were applied to classification of painful TMD, MIG, and HAT. CS was assessed through the central sensitization inventory (CSI), wind-up ratio (WUR), pressure pain thresholds (PPT), and the conditioned pain modulation test (CPM). Psychosocial factors were evaluated by validated instruments. Results: There was a significant difference regarding gender, with more women in the group TMD + MIG + HAT (p = 0.028). TMD + MIG and TMD + MIG + HAT had significantly lower PPTs than the TMD group. No group differences were found for the WUR, CPM, or CSI. TMD + MIG + HAT had higher chronic pain intensity (p = 0.001), disability points (p = 0.045), graded chronic pain scale (p = 0.007), and higher somatization (NSPS) scores (p = 0.012), compared to the other groups. Conclusion: Mechanical hyperalgesia was more pronounced in the group with the highest pain and somatization scores, while CPM and WUR did not differ between groups. Altered somatosensory function and CS may partially underlie the pathophysiology of overlapping TMD pain conditions, pointing towards additive effects of comorbid head pains. Clinical relevance: Our results demonstrate the importance of considering the association of primary and secondary headaches during TMD assessment and its implications for maintaining the signs and symptoms of CS. This can influence the conduct of treatment, which must be multidisciplinary, and must include management of mechanisms related to CS.